Problemas de fertilización en el Capo Cerrado de la parte central oriental de Brasil - Hardy, Frederick (Instituto Interamericano de Ciencias Agrícolas (IICA), 2025)
The climatic conditions in the Campo Cenado of cast-central Brazil fator the grouth of Evergreen Moist Forest but the present-day regetation comprises shrub-grass savanna consequent on forest felling and burning which preceeded agricultural exploitation and the loss of surface soil by erosion. The Campo Cerrado soil is alas-sed as Red and Reddish-Brown Latosol or av a neu group, Rubrozem, having vela-tionship with Reddish-Yellou Podzolic soil The soil bas lou organic matter and nitrogen contents Its reaction value is generally belou pH 50 Exchangeable calcium is particularly low and also certain minor nutrient elements, notably sulphur, zinc and molybdenum Phosphate is the most deficient available nutrient of all Pot-tests gave results in accord with those of chemical soil analysis Fertilizes field experiments gate results in accord whith those of the pot-tests, they showed response to sulpbm and to zinc among the minos elements, but particularly to phosphate They also showed response to dolomitic limestone In order to resuscitate the Campo Cerrado soils cheaply and rapidly, minimal amounts of ground rock phosphate, dolomitic limestone, gypsum and a minor element mixture, preferably chelates, should be applied. This should encourage the regeneration of the original forest and raise the level of organic matter and nitrogen in the smface soil The base exchange capacity and the retentivity o the soil for nutrients and water should thereby be increased In place of limestone, 23psum and minor elements, ground basic igneous rock (eg basalt) might be applied Agricultural development of the regenerated organic soil might afterward most evo-nomically be effected by shifting cultivation on the conidos system Alternatit ely the forest might be felled and agricultural crop rotations initiated with the help of mixed fertilizers, including minor elements, and leguminous contes crops ubere feasible and financially economical.